الهيمنة الحضرية والطابع العمراني - اليحياوي, شهاب (جامعة الوادي - University of Eloued, 2020)
ملخص : تطرح الورقة المقترحة إشكالية تأثيرات السياسات التنموية وبرامج إعادة التهيئة والتوسعة العمرانية التي تنجز في الفضاء التاريخي الذي هو المدينة التقليدية وما تفرزه من ظواهر حضرية مرضية مثل ازدواج والتداخل التقليدي والحديث على صعيد العمراني والجمالي من المعمار التاريخي في المدينة التقليدية العربية من جهة وعلى صعيد الاستعمال الذي يقيمه الفرد المديني للفضاء الخاص والعام، الداخل والخارج، الظاهر والمخفي. والذي يكشف عن ازدواجية تواجد التقليدي ضمن الحديث والحديث ضمن التقليدي. لذلك نريد من خلال هذه الورقة ان ندرس هذا التداخل والازدواج على مستوى العمراني والجمالي والاستعمال المجالي للخاص والعام وللداخل والخارج في تواصل مع الموروث القيمي والرمزي لشاغلي الفضاء المديني بشكليه التقليدي والحديث. وقد اعتمدنا في دراستنا على المنهج الكيفي واخترنا تقنية المقابلة والملاحظة المباشرة لتجميع البيانات والمعطيات التي سنختبر من خلالها فرضية البحث الرئيسية التي مفادها ان الفضاء يتحدّد شكله ووظيفته عبر الاستعمال اليومي من قبل شاغليه الذين يتواصلون مع هذا الفضاء من خلال هابتوس فضائي يحيلنا الى الجماعة الاجتماعية المرجع ويتواصلون عبره مع الآخر رمزيا لا ماديا، اعتبارا لأنّ استعمال المجال دالّ على مسايرته او عدم مسايرته للقيم والمعايير المستبطنة. فالمجال حمّال لخطاب سيميولوجي يفضح تأويله درجة الرباط الاجتماعي لشاغله وتواصله مع بيئته الحضرية تأثّرا وتأثيرا. وسنختبر هذه الفرضية بالنظر الى الاستعمال الذي يقيمه الفاعلون لواجهة المسكن الحضري ضمن المدينة التقليدية في تواصلهم مع ذاكرتهم الفضائية الجماعية ورأسمالهم الرمزي الذي يسقطونه على ما هو ماديّ (المعمار) ليتحوّل الى لغة للتواصل أي سيميولوجية الفضاء والتواصل الاجتماعي داخل الفضاء المديني. كما سنختبر هذه الفرضية على صعيد استعمال الداخل أي توزيع الغرف واستعمالاتها بالنظر الى المروفولوجية الأصلية لهذا الداخل. Abstract : In this paper we treat the problems and effects of development policies , rehabilitation programs and the urban expansion accomplished in the traditional city as a historical space and what it engenders from satisfactory urban phenomenons like duplication and interference bebtween the traditional and the modern on the urban and aesthetical level of historical architecture in the traditional arab city on a hand and the level of use assessed by the urban individual of private and public space, both on the outside and inside, the visible and the hidden which reveals the presence of the traditional within the modern and also modern within the traditional. That’s why we want to study through this paper the interference and duplication on the urban and aesthetical level and use of private and public spaces in the inside and the outside in relation with the symbolic and value inheritance for the civil space occupiers in both its forms : traditional and modern . We adopted in our study the qualitative approach and we chose the meeting and direct observation method to collect data and information that will be used to test the principal search hypothesis aiming to show us that both the shape and the function of the space are determined through the daily use by its users who communicate through spacial habitus referring us to the social community and used to communicate with others symbolically and not physically , considering that the use of space indicates the presence or lack of underlying values and criteria . In fact the field holds a symiologic speech whose interpretation exposes the degree of social cohesion of its occupant and his communication with the environment either affecting it or getting affected by it Moreover we will test this hypothesis by observing the actor’s use of the facade of urban housing within the traditional city in their connection with the collective space memory and symbolic capital projected on material (architecture) so that it becomes a language of communication wich means symiological space and social communication within the urban space. We will also test this hypothesis on the interior use level: like the distribution of rooms and their uses in view of the original morphology of this interior.
نصيّة المعمار وسيميولوجيا التواصل
مقال
Keywords: الهيمنة الحضرية ; الاستعمال ; المجال الخاص ; المعيش ; الذاكرة المجالية; urban dominance, use, private space, daily pension, spatial memory